2004
DOI: 10.1001/archinte.164.18.2005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Therapy for Critically Ill Hospitalized Patients

Abstract: Insulin therapy initiated in the hospital in critically ill patients has a beneficial effect on short-term mortality in different clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(39 citation statements)
references
References 65 publications
0
37
0
1
Order By: Relevance
“…Intensive control of blood glucose has been used in a number of acute settings with variable results. A meta-analysis of 35 (n = 8,478) clinical trials of acute insulin administration revealed a statistically significant 15% reduction in mortality comparing insulin intervention with controls (RR 0.85, 95% CI: 0.75–0.97) [50]. Analysis of sub-groups revealed a 29% mortality benefit for strict glucose control (RR 0.71, 95% CI: 0.54–0.93), while studies in which insulin was administered without a target reduction in glycaemia found no mortality benefit [50].…”
Section: Hyperglycaemia and Critical Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive control of blood glucose has been used in a number of acute settings with variable results. A meta-analysis of 35 (n = 8,478) clinical trials of acute insulin administration revealed a statistically significant 15% reduction in mortality comparing insulin intervention with controls (RR 0.85, 95% CI: 0.75–0.97) [50]. Analysis of sub-groups revealed a 29% mortality benefit for strict glucose control (RR 0.71, 95% CI: 0.54–0.93), while studies in which insulin was administered without a target reduction in glycaemia found no mortality benefit [50].…”
Section: Hyperglycaemia and Critical Illnessmentioning
confidence: 99%
“…A meta-analysis of 35 (n = 8,478) clinical trials of acute insulin administration revealed a statistically significant 15% reduction in mortality comparing insulin intervention with controls (RR 0.85, 95% CI: 0.75–0.97) [50]. Analysis of sub-groups revealed a 29% mortality benefit for strict glucose control (RR 0.71, 95% CI: 0.54–0.93), while studies in which insulin was administered without a target reduction in glycaemia found no mortality benefit [50]. Similarly, those studies in which insulin was administered as GKI showed no statistically significant benefit, while studies administering insulin in other ways (mostly as sliding scale) did show a 27% mortality reduction (RR 0.73, 95% CI: 0.56–0.95) [50].…”
Section: Hyperglycaemia and Critical Illnessmentioning
confidence: 99%
“…A growing body of evidence indicates that treatment of hyperglycemia improves clinical outcome (11). In a prospective randomized trial in Leuven, postoperative patients were treated with an intensive insulin protocol (12).…”
mentioning
confidence: 99%
“…A near-significant trend toward decreasing mortality was seen in patients with acute myocardial infarction who did not receive reperfusion therapy. The authors concluded that insulin therapy initiated in the hospital in critically ill patients has a beneficial effect on short-term mortality in different clinical settings [31].…”
Section: The Importance Of Glycemic Controlmentioning
confidence: 99%